Imidazolium-Based Lipid Analogues and Their Interaction with Phosphatidylcholine Membranes - Wang, Da (Langmuir : the ACS journal of surfaces and colloids, 2016)
4,5-Dialkylated imidazolium lipid salts are a new class of lipid analogues showing distinct biological activities. The potential effects of the imidazolium lipids on artificial lipid membranes and the corresponding membrane interactions was analyzed. Therefore, 1,2-dipalmitoyl-sn-glycero-3-phosphocholine (DPPC) was employed to create an established lipid monolayer model and a bilayer membrane. Mixed monolayers of DPPC and 4,5-dialkylimidazolium lipids differing by their alkyl chain length (C7, C11, and C15) were characterized by surface pressure-area (π-A) isotherms using a Wilhelmy film balance in combination with epifluorescence microscopy. Monolayer hysteresis for binary mixtures was examined by recording triplicate consecutive compression-expansion cycles. The lipid miscibility and membrane stability of DPPC/imidazolium lipids were subsequently evaluated by the excess mean molecular area (ΔAex) and the excess Gibbs free energy (ΔGex) of mixing. Furthermore, the thermotropic behavior of mixed liposomes of DPPC/imidazolium lipids was investigated by differential scanning calorimetry (DSC). The C15-imidazolium lipid (C15-IMe·HI) forms a thermodynamically favored and kinetically reversible Langmuir monolayer with DPPC and exhibits a rigidification effect on both DPPC monolayer and bilayer structures at low molar fractions (X ≤ 0.3). However, the incorporation of the C11-imidazolium lipid (C11-IMe·HI) causes the formation of an unstable and irreversible Langmuir-Gibbs monolayer with DPPC and disordered DPPC liposomes. The C7-imidazolium lipid (C7-IMe·HI) displays negligible membrane activity. To better understand these results on a molecular level, all-atom molecular dynamics (MD) simulations were performed. The simulations yield two opposing molecular mechanisms governing the different behavior of the three imidazolium lipids: a lateral ordering effect and a free volume/stretching effect. Overall, our study provides the first evidence that the membrane interaction of the C15 and C11 derivatives modulates the structural organization of lipid membranes. On the contrary, for the C7 derivative its membrane activity is too low to contribute to its earlier reported potent cytotoxicity